Some psychometric properties of the Icelandic versions of very Short Health Anxiety Inventory (VSHAI) and the Medically Unexplained Symptoms Checklist (MUSC) - Jón Viðar Viðarsson 1986- (2016)
Verkefnið er handrit af tímaritsgrein og verður því lokað til 3.6.2019 The prevalence of health anxiety and medically unexplained symptoms (MUS) is unknown in Iceland and currently no instruments are available in Icelandic that reliably measure these symptoms. In other countries MUS are estimated to account for a third of primary healthcare visits and health anxiety can be diagnosed in up to a quarter of secondary healthcare patients. Health anxiety and MUS can seriously interfere with daily functioning and lead to increased healthcare utilization with limited results. Cognitive behavior therapy (CBT) is effective for health anxiety and some types of MUS. Screening instruments for MUS and health anxiety can facilitate diagnosis and referral to effective interventions. The primary aim of the study was to evaluate the psychometric properties of two questionnaires that were translated from English to Icelandic; The Very Short Health Anxiety Inventory (VSHAI) and the Medically Unexplained Symptoms Checklist (MUSC). Psychometric properties of the Icelandic versions of questionnaires were evaluated in a student sample and a clinical sample. Participants were 200 undergraduates at the University of Reykjavik and 182 patients at the cardiology department of Landspitali - The National University Hospital of Iceland. Two week test-retest reliability in the student sample was high for the VSHAI, but inadequate for the MUSC. The MUSC failed to reliably detect MUS between administrations. Internal consistency of the VSHAI was good in both samples. The psychometric properties of the Icelandic VSHAI were adequate and similar to previous studies on the English Short Health Anxiety Inventory (SHAI). The VSHAI needs to be investigated for its validity. The MUSC requires revisions followed an examination of its psychometric properties.